Effect of the cation sublattice composition of tin-based type-I clathrates on their low-temperature thermal properties. Issue 32 (27th July 2018) - Novikov, V. V.; Pilipenko, K. S.; Matovnikov, A. V.; Mitroshenkov, N. V.; Likhanov, M. S.; Tyablikov, A. S.; Shevelkov, A. V.
Abstract : We performed an experimental study on thermal properties of the Sn18 In6 As21.5 I8 clathrate by measuring temperature dependencies of its heat capacity (2–300 K) and thermal expansion (5–300 K). Abstract : We performed an experimental study on thermal properties of the Sn18 In6 As21.5 I8 clathrate by measuring temperature dependencies of its heat capacity (2–300 K) and thermal expansion (5–300 K). By comparing the results with those published previously for Sn-based clathrates Sn24 P19.2 I8, Sn20 Zn4 P20.8 I8, and Sn17 Zn7 P22 I8, we established that partial replacement of tin and phosphorus by heavier indium and arsenic, respectively, leads to lowering vibration frequencies in both host and guest substructures. Deviation of the observed thermal properties at low temperatures from those predicted by the Einstein–Debye model is caused by the Schottky-like contribution of two-level systems to heat capacity and thermal expansion. These systems form owing to transitions of guest atoms in non-spherical 24-vertex cages between stationary states with close energies.